Treatment of Forty Adult Patients with Hodgkin Disease; Baghdad Teaching Hospital Experience - Abbas, Mohammed S.; Naji, Alaadin S.; AL - Saffar, Ahmed A.; Shubbar, Mazin A.; Matti, Bassam F.; Siwan, Adil; Majeed, Ammar F.; Jawad, Ali M. (Journal of the Faculty of Medicine Baghdad, 2015)
Background: Hodgkin disease was the first cancer in which the curative potential of combination chemotherapy was demonstrated. The affected patients are often young and there is a great potential for adding years of productive life by giving curative therapy even when the disease is advanced.Objective: to describe the experience of the hematology unit,Baghdad Teaching Hospital, in the management of 40 adult patients with Hodgkin disease.Patients and Methods: a retrospective cohort study of forty adult Iraqi patients with Hodgkin disease between 2005 and 2013 in the hematology unit. Patients were treated initially with 6-8 cycles of ABVD chemotherapy protocol (doxorubicine+ bleomycin+ vinblastin+ dacarbazine) , nine patients received additional involved field radiotherapy for residual masses or bulky disease. Overall survival and progression free survivals were estimated using Kaplan Meier survival plot.Results: The mean age was 28.6±12.88 years with females forming 61.5% of patients, mean duration of follow up was 27.9± 20.6 months. Staging showed that 55% and 27.5% had stage II and III respectively. B symptoms were found in 72.5% patients , bulky disease in 42.5% patients. Complete Response+ Complete Response undetermined was seen in 85% of cases. First Relapse occurred in 14%, and death in 7.5% of the patients. The 8 year overall survival and progression free survival were 82% and 50% respectively while the mean overall survival and progression free survival times were 84.7 and 59.9 months respectively.Conclusion: The results of the treatment of adult patients with Hodgkin disease in our unit is rather comparable to the results from other studies.